A novel phytoremediation index for aquatic systems contaminated by toxic elements. Issue 1 (2nd January 2023) - Pereira, Fabricio José; Castro, Evaristo Mauro de
Abstract: Deposition of potentially toxic elements causes environmental pollution and health problems. Phytoremediation is one of the methods used for scavenging such pollutants from polluted sites. Establishing the time needed to decontaminate a system is a challenge to overcome. This study presents a new phytoremediation index (PI) which was used as a tool to manage the system. The model was developed based on the relative growth rate and the capacity of plants to retain the pollutant in their biomass. The index was tested in modified nutrient solution containing arsenic, cadmium, and lead and in Pistia stratiotes plants. The PI was used to predict the time needed to complete the removal of toxic elements. The model showed a significant correlation between the treatments and the accumulation of the elements by plants. Therefore, the PI is an efficient tool for the management and remediation of aquatic systems contaminated by toxic elements.